Reduction in maternal anxiety following prenatal pediatric urology consultation - Yang, Jessica; Baker, Zoë; Dillon, Hannah; Hannallah, Arthi; Klecha, Irene; SooHoo, Michelle; Ko, Joan; De Filippo, Roger; Vasquez, Evalynn (Frontiers in Urology, 2023)
Introduction Fetal anomalies detected on prenatal ultrasound can elicit maternal psychological distress and may be associated with increased risk of adverse fetal outcomes. Prenatal consultation with pediatric specialists may allay parental worries by improving clarity surrounding a fetal diagnosis, establishing a postnatal management plan, and providing expert advice. We sought to determine whether maternal anxiety and worry decreased following prenatal pediatric urology consultations among a cohort of pregnant women whose fetuses were diagnosed with urologic anomalies. Methods Pregnant women referred to pediatric urologists for prenatal consultation through our Fetal Maternal Center following detection of a urologic anomaly were recruited from February 2021 to March 2022 inclusive. Participants completed questionnaires before and after prenatal pediatric urology consultation assessing maternal current state anxiety (S-Anxiety) on the State-Trait Anxiety Inventory (STAI) and self-reported worry surrounding the fetal diagnosis. Differences in anxiety and worry before versus after prenatal consultation were analyzed using paired t-tests and McNemar’s tests. Results 26 pregnant women completed pre- and post-visit questionnaires. Most participants (92.3%) received prenatal pediatric urology consultation for anomalies of the fetal kidney(s), including hydronephrosis and suspected multicystic dysplastic kidney. The proportion of participants reporting extreme or moderate levels of worry surrounding the fetal diagnosis significantly decreased from 69.2% prior to prenatal pediatric urology consultation, to 30.8% after consultation (p=0.02). Reductions in worry after prenatal consultation were reported among 80.8% of participants. Average state anxiety on the STAI similarly significantly decreased from 35.2 ( ± 9.4) before prenatal consultation to 31.4 ( ± 11.1) after consultation. Differences in reductions in anxiety and worry did not significantly differ among participants attending prenatal consultations in-person or via telehealth. Conclusions Among a cohort of pregnant women diagnosed with fetal anomalies of the urinary tract, anxiety and worry surrounding the fetal diagnosis significantly decreased after prenatal in-person or telehealth consultations with pediatric urologists.